2020
DOI: 10.2147/cmar.s260915
|View full text |Cite
|
Sign up to set email alerts
|

<p>EGLIF-CAR-T Cells Secreting PD-1 Blocking Antibodies Significantly Mediate the Elimination of Gastric Cancer</p>

Abstract: To investigate the anti-tumor effects of programmed cell death protein 1 (PD-1) scFv-secreting EGFR-chimeric antigen receptor-modified (CAR)-T cells against gastric cancer. Methods: Second-generation EGFR-CART cells and fourth-generation PD-1 scFvsecreting EGFR-CART cells were engineered. The anti-tumor activities of chimeric antigen receptor-modified (CAR)-T cells were analyzed in vitro by long-term co-culture with gastric cancer cells. The tumor scavenging capacity in vivo was evaluated in xenograft and PDX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…One study found that anti-PD-1 scFv secretion by CAR T-cells enhanced proliferation of the CAR T-cells and also reduced PD-1 expression on CAR T-cells in vitro, which can further reduce inhibition. 79 Additionally, anti-PD-1 scFv secretion was seen to enhance CAR T-cell anti-tumor function in a gastric cancer mouse model. 79 Similar effects of anti-PD-1 scFv secretion by CAR T-cells were reported in another study, which showed this increased T-cell cytokine production and proliferation in vitro, while in vivo there was enhanced anti-tumor efficacy and CAR T-cell accumulation in the TME.…”
Section: Armored Car T-cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…One study found that anti-PD-1 scFv secretion by CAR T-cells enhanced proliferation of the CAR T-cells and also reduced PD-1 expression on CAR T-cells in vitro, which can further reduce inhibition. 79 Additionally, anti-PD-1 scFv secretion was seen to enhance CAR T-cell anti-tumor function in a gastric cancer mouse model. 79 Similar effects of anti-PD-1 scFv secretion by CAR T-cells were reported in another study, which showed this increased T-cell cytokine production and proliferation in vitro, while in vivo there was enhanced anti-tumor efficacy and CAR T-cell accumulation in the TME.…”
Section: Armored Car T-cellsmentioning
confidence: 97%
“… 79 Additionally, anti-PD-1 scFv secretion was seen to enhance CAR T-cell anti-tumor function in a gastric cancer mouse model. 79 Similar effects of anti-PD-1 scFv secretion by CAR T-cells were reported in another study, which showed this increased T-cell cytokine production and proliferation in vitro, while in vivo there was enhanced anti-tumor efficacy and CAR T-cell accumulation in the TME. 80 …”
Section: Armored Car T-cellsmentioning
confidence: 97%
“…Therefore, a great deal of research has been carried out on the treatment of different cancers, such as liver cancer, cholangiocarcinoma and pancreatic cancer. Combined treatment integrating CAR T cell therapy with targeted therapies, such as therapies targeting CEA, HER2, GPC3, MUC1, CD133, EpCAM or EGFR, has exhibited great potential (107)(108)(109)(110).…”
Section: Car T Cell Treatmentsmentioning
confidence: 99%
“…• Secretion of anti-checkpoint antibodies [143][144][145][146][147] • Dominant negative checkpoint receptor expression 148 • Checkpoint receptor knockout/ downregulation [149][150][151][152][153][154][155] • Checkpoint switch receptors [157][158][159] Immunosuppressive cytokines Secretion of immunosuppressive cytokines by tumour and suppressive immune cells prevents optimal T cell activation and proliferation…”
Section: Tumour Resistance Mechanism Description and Challenge To Carmentioning
confidence: 99%
“…Secretion of anti-PD-L1 antibodies or scFvs by CAR T cells improved anti-tumour responses with reduced expression of exhaustion markers in multiple mouse models including a humanised mouse model of renal cell carcinoma and a patient-derived xenograft (PDX) model of gastric cancer. [143][144][145][146][147] In an alternative strategy, a dominant negative PD-1 receptor has been designed, consisting of PD-1 lacking the intracellular domain, and expressed in CAR T cells. The dominant negative receptor can outcompete endogenous receptors for PD-L1 on tumours.…”
Section: Overcoming Immune Checkpoints In Car T Cellsmentioning
confidence: 99%